Finance and growth : an investigation into the role of internal, bank and equity finance - Ghimire, Binam; Giorgioni, Gianluigi (Economics and Business Review, 2013)
This paper has used the findings of the recent World Bank Enterprise Survey to provide some, admittedly tentative, further evidence on the relationship between financial development and economic growth, by incorporating the impact of internal finance. The inclusion of the variable internal finance should go some way to mitigate the possible bias due to the omission of an important variable from empirical work. By doing so, we aimed at providing some further evidence either in favour or against two puzzling results emerging from recent empirical works. The first puzzle regards the negative impact of banks upon growth in the short-term, although the impact reverts to positive on the long-term. This puzzle is reinforced by seemingly contradictory evidence stemming from micro-level studies, which indicate a positive impact of external finance on firms' growth, while empirical tests at macro level do not unanimously support this positive impact. The second puzzle, concerns the relatively stronger impact of stock markets upon growth. Given the objective difficulties and costs encountered in accessing both bank credit and equity as documented in the paper, the above puzzles required further tests. Our, tentative, results provide some evidence that banks still have a negative impact upon short-term growth, while stock markets do not appear to contribute to growth in a significant manner once the effect of internal finance is included. Finally, internal finance itself does not appear to boost growth in a statistically significant manner. These tentative findings are in need of further research. (original abstract)